Experimental Characterization of Traditional Mortars and Polyurethane Foams in Masonry Wall. (19th August 2018) - Foti, Dora; Lerna, Michela; Vacca, Vitantonio
Abstract : Masonry is a composite material largely used in construction. It exhibits several advantages, including significant compressive strength, thermal inertia, and aesthetic beauty. A disadvantage of masonry is mainly related to the inadequate shear strength due to the poor capacity and ductility of the adopted mortar. This aspect is crucial in seismic areas. In this paper, the behavior of polyurethane foams, used as adhesives for the construction of thin joints brick masonry walls, has been investigated. First, the characterization of components was carried out, followed by laboratory uniaxial tests on masonry walls and shear tests on triplets. Moreover, a comparison of the behavior of the foam-brick walls with respect to the traditional mortars masonry was carried out, as the type of joints varies and the arrangement of the holes of the bricks varies with respect to the direction of the applied load. Results provide indications on which adhesive has to be adopted for masonry buildings in reference to the site of construction (i.e., seismic hazard).